PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI BANK KAL - Any Mardiani; Maya Sari Dewi (Universitas Lambung Mangkurat, 2015)
The research method used explanatory quantitative research, with 334 people population. Sampling technique used was simple random sampling and stratified random sampling with the samples of 182 people who served as respondents. For data analysis, the tool used was multiple linear regression (multiple Linear Regression) using SPSS software ver. 19.0. The results of this study concluded that the variables of job satisfaction and organizational commitment had significant positive effects on the performance of the employees of Bank Kalsel both simultaneously and partially